2016
DOI: 10.2497/jjspm.63.976
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Li<sub>3</sub>PS<sub>4</sub> Solid Electrolyte by Liquid-Phase Shaking Using Organic Solvents with Carbonyl Group as Complex Forming Medium

Abstract: Li 3 PS 4 was synthesized from the reaction of Li 2 S and P 2 S 5 in several kinds of organic solvents with a carbonyl group, i.e. dimethyl carbonate (DMC), ethyl acetate (EA) and methyl propyl ketone (MPK) as a complex forming medium by liquid-phase shaking. XRD results showed that Li 2 S still existed in the sample prepared using MPK, whereas the reaction between Li 2 S and P 2 S 5 completed in DMC and EA media which then resulted in the formation of co-crystalline complex for EP and low crystalline complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…However, solution processing leads to LPSsolvent complexes that require temperatures as high as 100 C to remove the solvent and form pure LPS. 38,[41][42][43][44] Furthermore, solution processed LPS leads to ionic conductivities that are lower than those obtained using ball milling. 44 Finally, LPS stability in solvents is also of concern as recent reports have shown that Li 7 P 3 S 11 decomposes in polar solvents such as acetonitrile and dimethylformamide (DMF).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, solution processing leads to LPSsolvent complexes that require temperatures as high as 100 C to remove the solvent and form pure LPS. 38,[41][42][43][44] Furthermore, solution processed LPS leads to ionic conductivities that are lower than those obtained using ball milling. 44 Finally, LPS stability in solvents is also of concern as recent reports have shown that Li 7 P 3 S 11 decomposes in polar solvents such as acetonitrile and dimethylformamide (DMF).…”
Section: Introductionmentioning
confidence: 96%
“…LPS has four reported phases: amorphous and a, b, and g-crystalline, with the amorphous form reporting the highest conductivity, ranging from 3-4 Â 10 À4 S cm À1 at 25 C. 37 The b-crystalline form has a conductivity of approximately 1.5 Â 10 À4 S cm À1 , whereas the g-crystalline form reports a much lower conductivity (10 À6 S cm À1 ). 38 Additionally, the a and g forms of LPS are synthetically more difficult to access than the amorphous or bcrystalline forms, making them less attractive candidates for solid state electrolytes. 39,40 LPS can be synthesized using solution processing or ball milling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structures can, through various pathways, have strain that may lead to change in the lattice volume and thus differences in the [37][38][39][40][41][42][43] Li 1+x Al x Ge 2Àx (PO 4 ) 3 , [44][45][46][47][48][49][50][51] Li 6 PS 5 Cl, 14,[52][53][54][55] Li 3 PS 4 , [56][57][58][59][60][61] (Li 2 S) x -(P 2 S 5 ) 100Àx , [62][63][64][65] ability to conduct ions. 81,88 It is worth mentioning here that use of solid electrolytes in lithium ion battery does not solve the problem of lithium dendrite formation and cell short circuiting.…”
Section: Strainmentioning
confidence: 99%
“…It is also worth mentioning that nanoporous β-Li 3 PS 4 was synthesized using a liquid-phase synthesis from reaction of Li 2 S and P 2 S 5 in tetrahydrofuran. We also studied the reaction of the Li 2 S–P 2 S 5 –LiI system by liquid-phase shaking using a variety of ester-group-containing solvents and obtained nanosized solid electrolytes, which were useful to increase the active material loading in the electrode composite [8, 9, 10]. These results motivated us to attempt to prepare c-Na 3 PS 4 using an ester solvent, to determine if c-Na 3 PS 4 could be synthesized through a suspension route, as we demonstrated with Li 2 S–P 2 S 5 –LiI solid electrolytes.…”
Section: Introductionmentioning
confidence: 99%